Analisis Sektor Unggulan Sebagai Daya Saing Dalam Pembangunan Wilayah Kawasan Ajatappareng Sulawesi Selatan - Khusnul Khatimah; Sri Astuty; Abdul Rajab; Muhammad Syafri; Irwandi (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
The process of regional development is strategically supported by leading sectors. The objectives of this study are to categorize economic sectors in the Ajatappareng region, identify leading sectors, and examine the dynamics of development within economic sectors. The Central Statistics Agency (BPS) provided secondary statistics on the GDRP of South Sulawesi Province and the Ajatappareng area (Parepare City, Pinrang, Sidrap, Barru, and Enrekang Regency) for the years 2020–2024. Klassen Typology, Shift-Share analysis, and Location Quotient (LQ) analysis are among the analytical methods employed. According to the study's findings, the primary industries in the Ajatappareng region include manufacturing, government administration, defense, and mandatory social security; wholesale and retail commerce; and agriculture, forestry, and fishing.